Comparison of dexmedetomidine alone or with other sedatives for paediatric sedation during magnetic resonance imaging: a systematic review - Rudy Vitraludyono; Arie Utariani; Elizeus Hanindito (Medicinski glasnik, 2022)
Aim: To compare the outcome of sole dexmedetomidine or with other sedative drugs in paediatric patients during magnetic resonance imaging (MRI). Methods: Literature was obtained from PubMed and ScienceDirect from 2010-2020 using key words: sedation, paediatric, dexmedetomidine, ambulatory, MRI, ketamine, propofol, midazolam. The literature selection was based on Participant, Intervention, Comparators, Outcomes (PICO) analysis. All English full-text and peer-reviewed articles were included. The primary outcome was hemodynamic stability, respiratory compromise, and recovery time. The risk of bias analysis was assessed using Cochrane collaboration Risk of Bias (RoB 2.0). Result: Of 106 studies, 17 studies were included with a total 3.430 paediatric patients undergoing MRI. Dexmedetomidine alone provides a more stable hemodynamic but longer recovery time than ketamine, propofol or midazolam. The combination of dexmedetomidine and ketamine provides more stable hemodynamics, especially in the incidence of hypotension and bradycardia, and does not significantly reduce airway configuration more than sole dexmedetomidine or ketamine. Intranasal dexmedetomidine is more recommended than its combination with midazolam. Combining dexmedetomidine with ketamine, propofol or midazolam provides a shorter recovery time. Conclusion: A combination of dexmedetomidine with other sedatives such as ketamine, propofol and midazolam is better than sole dexmedetomidine for paediatric sedation during magnetic resonance imaging.
Keywords: anaesthesia; ketamine; midazolam; propofol